Saberes e práticas de saúde em campo: um olhar antropológico sobre a estratégia de saúde da família na Praia Azul - SP - Coelho, Juliana Affonso Gomes (2011)
The purpose of this research was originally the anthropological study of multidisciplinary teams of Family Health Program (PSF), realized from ethnography in a city of São Paulo, in which I intend to observe the interaction between different discursive fields and professional practices. It was noted, however, that the multidisciplinary teams studied could be divided into two types of teams: a hierarchical, formed by all legitimate health professionals (doctors, nurses and nursing assistants), and a more egalitarian, just conformed by Community Health Agents (ACS). Moreover, by exploring the theme through ethnographic research, was also shown that knowledge and health practices in the field were crossed by the paradigm of health promotion, which not only sought to reorient the demand of users of public health, but sought to transform them, through educational processes, in subjects of citizenship. For this, an analysis of this process was made, focusing particularly on the role and training of ACS, since they emerged not only as mediators between biomedical knowledge and popular knowledge, but also showed themselves capable of switching between these two roles: the interventionist state and the interlocutor of the community. Thus, if the ambiguity of the ACS reveal, on hand, the normative character of the strategy, on the other hand, showed an opening for the emergence of citizenship, which allowed the problematization of the health citizention project implicit in public health politics, as the coexistence of contradictory models within the same program and the same health equipment. Then we saw that the Family Health Strategy presents paradoxes and inconsistencies in the operationalization of the program, some of which may bind that it consolidates as a guideline of SUS and must be object of reflection, in order that the program does not become just a model manager without the effective care counterparty expected of a health care service in public health.